Social Media As An Instrument To Encourage The Consumption Of Halal Products - M.Ilham; Muhammad Fakhri Khairi; Khoirudin; MHD. Nanang Hidayat (LP2M IAIN Palopo, 2026)
The development of social media has brought significant changes in communication patterns, marketing, and consumption behavior among Muslim communities, including in the selection of halal products. This study aims to analyze the role of social media as an instrument in shaping halal awareness, constructing a halal lifestyle, and influencing consumption behavior and purchasing interest in halal products in the digital era. The study used a literature review approach through the study and synthesis of various previous research results relevant to the themes of social media, halal lifestyle, and Muslim consumer consumption behavior. The analysis was conducted using content analysis techniques to identify patterns of relationships, similarities, and differences in findings between studies. The results of the study indicate that social media functions as an effective agent of halal socialization through the dissemination of halal certification information, educational content, and Islamic lifestyle narratives packaged visually and interactively. Social media exposure encourages the internalization of halal values, which are then integrated into consumer identity and preferences as part of a halal lifestyle. Furthermore, social media also influences consumption behavior and purchasing interest through the mechanisms of perception formation, trust, social influence from influencers and digital communities, and the construction of symbolic meanings for halal products. However, consumption of halal products in the digital era is driven not only by religious awareness but also by trends, social image, and the appeal of content, which have the potential to trigger consumer behavior. This research confirms that social media is a multidimensional instrument that connects religious values with digital market dynamics and plays a role in shaping the norms and practices of halal consumption in modern Muslim communities.